Novel biomarkers in the diagnosis of acute coronary syndromes: the role of circulating miRNAs. (September 2014) - Rognoni, Andrea; Cavallino, Chiara; Lupi, Alessandro; Secco, Gioel Gabrio; Veia, Alessia; Bacchini, Sara; Rosso, Roberta; Rametta, Francesco; Bongo, Angelo Sante
<x xml:space="preserve">Abstract</x> Cardiovascular disease, in particular acute coronary syndromes (ACS), is still one of the leading causes of death in industrialized countries. ACS including ST-elevation myocardial infarction (STEMI), non-ST-elevation myocardial infarction (NSTEMI) and unstable angina pectoris (UA) are associated with lower mortality if diagnosed early. The diagnosis is based on clinical symptoms, ECG and circulating biomarker-level changes. Recent studies have shown that there are alternatives to the known biomarkers such as ultrasensitive troponin I or T and creatine kinase Mb; there are, in fact, novel biomarkers such as miRNAs. These are 22-nucleotide-long non-coding RNAs that regulate gene expression at post-transcriptional level. Several recent studies have shown that miRNAs play a physiological role in cardiovascular homeostasis and in the pathogenesis of cardiovascular disease. Expression-pattern studies of myocardial tissue reveal that several miRNAs are up- or down-regulated during myocardial infarction. The purpose of the present review is to highlight the state of the art and future views on this topic.